2011
DOI: 10.1103/physrevb.83.241101
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-analyzed resonant inelastic x-ray scattering of the orbital excitations in KCuF3

Abstract: We report a Cu K-edge resonant inelastic x-ray scattering (RIXS) study of orbital excitations in KCuF3. By performing the polarization analysis of the scattered photons, we disclose that the excitation between the eg orbitals and the excitations from t2g to eg exhibit distinct polarization dependence. The polarization dependence of the respective excitations is interpreted based on a phenomenological consideration of the symmetry of the RIXS process that yields a necessary condition for observing the excitatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…This is an analogous to spin-wave excitation in a magnetically ordered state. Several experimental observations of orbiton by optical and Raman spectroscopies, [3][4][5][6][7] x-ray scatterings [8][9][10][11][12] and other experimental probes, as well as theoretical supports [13][14][15][16][17] have been reported so far. Nonetheless, characteristics of orbiton have not been revealed yet.…”
Section: Introductionmentioning
confidence: 94%
“…This is an analogous to spin-wave excitation in a magnetically ordered state. Several experimental observations of orbiton by optical and Raman spectroscopies, [3][4][5][6][7] x-ray scatterings [8][9][10][11][12] and other experimental probes, as well as theoretical supports [13][14][15][16][17] have been reported so far. Nonetheless, characteristics of orbiton have not been revealed yet.…”
Section: Introductionmentioning
confidence: 94%
“…By rotating the polarization-analyzer crystal and the detector about the axis of the beam reflected by the energy-analyzer crystal by 90 , one can selectively measure horizontal or vertical components of the polarization. Ishii et al 57) used a flat pyrolytic graphite (PG) crystal for the Cu K-edge and found that the experimental reflectivity of the crystal was $0:02. This method is simple but the low reflectivity of the polarization-analysis crystal results in tremendously long accumulation times.…”
Section: Hard X-ray Regimementioning
confidence: 99%
“…176) On the other hand, the polarization analysis of hard x-rays was performed for the d-d excitations of KCuF 3 at the Cu Kedge. 57) From the polarization dependence, the excitation between the e g orbitals was successfully distinguished from the excitations from t 2g to e g . The polarization dependence of the respective excitations was interpreted on the basis of a phenomenological consideration of the symmetry of RIXS process that yields a necessary condition for observing the excitations.…”
Section: Technical Topicsmentioning
confidence: 99%
“…A collective orbital excitation in an orbital ordered state is widely recognized as an orbital wave or its quantized object termed "orbiton", which is realized as an analogy of magonon in magnetically ordered system. The orbiton has been experimentally observed in LaMnO 3 and KCuF 3 by using the Raman scattering [2] and the resonant inelastic x-ray scattering (RIXS) technique [3,4]. As well as the experimental studies, theoretical studies have also been done to explore the characteristics of "orbiton" [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%